The Intersection of Antimicrobial Stewardship, the Pharmaceutical Industry, and the Federal Legislature. (5th August 2022) - Gregory, Eric; Martin, Craig
Abstract: To mitigate the dangers of inappropriate antimicrobial use leading to increased multidrug-resistant organisms and mortality, antimicrobial stewardship programs have become a mainstay in many health systems. Unfortunately, some pharmaceutical manufacturers simultaneously have ended antimicrobial research and development efforts altogether due to suboptimal return on investments. An optimal and sustainable antimicrobial armamentarium requires a broad alliance between antimicrobial stewardship programs, the pharmaceutical industry, the legislature, and federal and state agencies. Public–private relationships such as the Combating Antibiotic-Resistant Bacteria Biopharmaceutical Accelerator (CARB-X) and legislative policies creating push and pull incentives, including the Generating Antibiotic Incentives Now (GAIN), Developing an Innovative Strategy for Antimicrobial-Resistant Microorganisms (DISARM), and Pioneering Antimicrobial Subscriptions to End Upsurging Resistance (PASTEUR) Acts, are each a step in the right direction, but more work remains. Understanding these legislative actions is imperative for all clinicians, as is teamwork from those involved in the antimicrobial field to develop and maintain the life cycle of each drug that harbors societal value. Abstract : An appreciation of legislative actions, such as push and pull incentives, is essential for infectious diseases stakeholders to maximize the impact of their practices. The effect of these legislative actions on health systems and the pharmaceutical industry is examined.